Gambaran Pasca Kemerdekaan pada Naskah Drama Awal&Mira - Pandiangan, Angellica Minarti Martogi; Andhini, Alfira; Purnamasari, Widiyani Kuspi; Nugroho, Rudi Adi (UPA Bahasa Universitas Tidar And HISKI Kedu, 2023)
This study aims to present a post-independence picture that is displayed in literary and artistic works, examples of drama scripts. As can be seen in the drama script